Effectiveness of a nurse-led case management home care model in Primary Health Care. A quasi-experimental, controlled, multi-centre study - Morilla-Herrera JC; Martin-Santos FJ; Gonzalo-Jiménez E; Morales-Asencio JM; Celdráan-Mañas M; Carrasco A Millán; García-Arrabal JJ; Toral-López I (BMC, 2008)
Abstract Background Demand for home care services has increased considerably, along with the growing complexity of cases and variability among resources and providers. Designing services that guarantee co-ordination and integration for providers and levels of care is of paramount importance. The aim of this study is to determine the effectiveness of a new case-management based, home care delivery model which has been implemented in Andalusia (Spain). Methods Quasi-experimental, controlled, non-randomised, multi-centre study on the population receiving home care services comparing the outcomes of the new model, which included nurse-led case management, versus the conventional one. Primary endpoints: functional status, satisfaction and use of healthcare resources. Secondary endpoints: recruitment and caregiver burden, mortality, institutionalisation, quality of life and family function. Analyses were performed at base-line, and at two, six and twelve months. A bivariate analysis was conducted with the Student's t-test, Mann-Whitney's U, and the chi squared test. Kaplan-Meier and log-rank tests were performed to compare survival and institutionalisation. A multivariate analysis was performed to pinpoint factors that impact on improvement of functional ability. Results Base-line differences in functional capacity - significantly lower in the intervention group (RR: 1.52 95%CI: 1.05-2.21; p = 0.0016) - disappeared at six months (RR: 1.31 95%CI: 0.87-1.98; p = 0.178). At six months, caregiver burden showed a slight reduction in the intervention group, whereas it increased notably in the control group (base-line Zarit Test: 57.06 95%CI: 54.77-59.34 vs. 60.50 95%CI: 53.63-67.37; p = 0.264), (Zarit Test at six months: 53.79 95%CI: 49.67-57.92 vs. 66.26 95%CI: 60.66-71.86 p = 0.002). Patients in the intervention group received more physiotherapy (7.92 CI95%: 5.22-10.62 vs. 3.24 95%CI: 1.37-5.310; p = 0.0001) and, on average, required fewer home care visits (9.40 95%CI: 7.89-10.92 vs.11.30 95%CI: 9.10-14.54). No differences were found in terms of frequency of visits to A&E or hospital re-admissions. Furthermore, patients in the control group perceived higher levels of satisfaction (16.88; 95%CI: 16.32-17.43; range: 0-21, vs. 14.65 95%CI: 13.61-15.68; p = 0,001). Conclusion A home care service model that includes nurse-led case management streamlines access to healthcare services and resources, while impacting positively on patients' functional ability and caregiver burden, with increased levels of satisfaction. Trial registration ISRCTN44054549